1984
DOI: 10.1016/0047-6374(84)90116-7
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-induced reversal of age-related declines of oxidative reactions, mitochondrial yield, and flavins in skeletal muscle of the rat

Abstract: The ability of gastrocnemius muscle homogenates to catalyze the oxidation of succinate, glutamate + malate, pyruvate + malate, palmitoyl-coenzyme A, decanoylcarnitine and palmitoylcarnitine in the presence of ADP decreased by approximately 32% in sedentary male Sprague-Dawley rats between the ages of 9 and 25 months. Following 21 weeks of treadmill training (running), such homogenates from 25-month-old animals catalyzed oxidations 55% more rapidly than those from 25-month-old sedentary rats, and 17% faster tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
1

Year Published

1985
1985
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 38 publications
3
22
1
Order By: Relevance
“…On the other hand, intermyofibrillar mitochondria, that provide ATP for muscle contraction, are less prone to oxidative damage. This could explain why it has been found that 2-year-old rats retain the capacity to increase skeletal muscle oxidative capacity and mitochondrial population density in response to endurance training [35]. …”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, intermyofibrillar mitochondria, that provide ATP for muscle contraction, are less prone to oxidative damage. This could explain why it has been found that 2-year-old rats retain the capacity to increase skeletal muscle oxidative capacity and mitochondrial population density in response to endurance training [35]. …”
Section: Discussionmentioning
confidence: 99%
“…In the latter, endurance training improved the oxidative metabolism of skele tal muscles [33], retarded the skeletal muscle atrophy [34], diminished the decrease of the cardiac output [10], and prevented the changes in the neuromuscular synapses [35]. In the central nervous system, physical activ ity counteracted the age-dependent decline in the striatal dopaminergic system [36], in creased the regional blood flow to motorrelated areas of the brain [37,38], and com pensated for the decrease of the muscarinic receptor density in the hippocampus [39], The neural plasticity persisted into old age and was sensitive to exercise training [40,41], The number of synaptic dendrites of pyramidal neurons was positively correlated with the amount of daily wheel running in rats starting to run at the age of 26 months [41], The effects of exercise training to the central nervous system are presumably me diated by both the improved cardiovascular function and by the higher aerobic capacity which maintain the cerebral circulation and the neurons supplying skeletal muscle fibers [30,41], The effectiveness of the training schedule used in the present study was shown by an enhanced myocardial response to (3-adrenergic stimulation [9].…”
Section: Discussionmentioning
confidence: 99%
“…Studies show that mitochondrial proteins are reduced with age (Beyer et al, 1984;Kerner et al, 2001). A lower UCP mRNA expression has been observed in the skeletal muscle of older rats (Barazzoni and Nair, 2001;Iritani et al, 2002).…”
Section: Discussionmentioning
confidence: 96%